2019
DOI: 10.1371/journal.pone.0221949
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the maize transcription factor ZmVQ52 accelerates leaf senescence in Arabidopsis

Abstract: Leaf senescence plays an important role in the improvement of maize kernel yields. However, the underlying regulatory mechanisms of leaf senescence in maize are largely unknown. We isolated ZmVQ52 and studied the function of ZmVQ52 which encoded, a VQ family transcription factor. ZmVQ52 is constitutively expressed in maize tissues, and mainly expressed in the leaf; it is located in the nucleus of maize protoplasts. Four WRKY family proteins—Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…The results showed that the expression of Zm00001d046728 was also repressed by salt stress but was not significantly different in the varying range between the two lines (Supporting Information: Figure ). Moreover, Zm00001d046728 encodes a VQ family transcription factor, which was involved in regulating leaf senescence (Yu, Lu, et al, 2019). Thus, we further analyzed the expression patterns of Zm00001d046729 in NIL −082 and NIL −Ye107 under salt stress condition and found that the expression of Zm00001d046729 was more easily to be induced in NIL −082 than in NIL ‐Ye107 plant (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the expression of Zm00001d046728 was also repressed by salt stress but was not significantly different in the varying range between the two lines (Supporting Information: Figure ). Moreover, Zm00001d046728 encodes a VQ family transcription factor, which was involved in regulating leaf senescence (Yu, Lu, et al, 2019). Thus, we further analyzed the expression patterns of Zm00001d046729 in NIL −082 and NIL −Ye107 under salt stress condition and found that the expression of Zm00001d046729 was more easily to be induced in NIL −082 than in NIL ‐Ye107 plant (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Our results revealed that TaWRKY40‐D plays roles in both JA‐ and ABA‐induced leaf senescence in wheat, which implies that TaWRKY40‐D may function as a key regulator of the cross‐talk between the JA and ABA signalling pathways. Although cross‐talk between JA and ABA has been previously described in Arabidopsis and maize, it is still unclear in wheat (Yu et al 2019; Zhang et al 2020b). Moreover, as TaWRKY40‐D itself is induced by the onset of leaf senescence, JA and ABA, we speculate that there is a complex feedback loop among JA‐ and ABA‐induced leaf senescence and TaWRKY40‐D , which is implicated in the fine‐tuning of leaf senescence timing and needs to be further investigated in detail in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf senescence is another developmental process potentially regulated by VQ proteins. The overexpression of maize ZmVQ52 in Arabidopsis accelerated premature leaf senescence ( Yu et al, 2019 ). Figure 1A summarizes what has been reported on the involvement of VQ proteins and WRKY transcription factors in regulating different processes throughout plant life cycle.…”
Section: Vq Proteins Regulation Of Developmentmentioning
confidence: 99%
“…The relationship of the senescence process and the production of NO is somehow controversial as both positive or negative correlation has been reported depending upon the organ or being natural or dark-induced ( Mishina et al, 2007 ; Ma et al, 2010 ; Niu and Guo, 2012 ; Liu and Guo, 2013 ; Du et al, 2014 ; Bruand and Meilhoc, 2019 ). Linked to ROS and NO action, ZmVQ52 associated to WRKY proteins regulate leaf senescence in maize ( Yu et al, 2019 ). Moreover, around 32% of the VQ genes and more than half of the WRKY genes were upregulated in Arabidopsis senescing leaves ( Schmid et al, 2005 ).…”
Section: Molecular Oxygen and Nitric Oxide Regulation On The Arabidopmentioning
confidence: 99%